At-Home Bioelectrical Impedance Analysis (BIA) Monitoring of Adult Females at Risk of Breast Cancer-Related Lymphedema: Nonrandomized One-Year Longitudinal Feasibility Study - Cheri Teranishi-Hashimoto; Monica Padilla; Yoomi Heo; Lori Bravi (JMIR Formative Research)
Abstract BackgroundBreast cancer, the most common type of diagnosed cancer in women worldwide, is often associated with the development of lymphedema as a treatment-related effect. Patients undergoing surgery, radiation, or chemotherapy present a higher risk for this side effect. Historically, patients are often not referred to rehabilitation for lymphedema management until the swelling is visible and has progressed, which reduces the chance of reversing the disease progression. Surveillance is key to identifying the earliest signs of breast cancer–related lymphedema, initiating treatment, reversing the disease process, and reducing the impact on function. ObjectiveThe primary goal of this study was to assess the feasibility of monitoring fluid levels in patients with cancer using a bioimpedance analysis home device and to detect any relevant changes that may correlate with an increased risk of developing lymphedema. Remote monitoring by a clinician has not previously been possible, and a comparable bioelectrical water analyzer device has never been available to patients within the comfort of their homes. MethodsThe study included 8 adult patients diagnosed with unilateral breast cancer who underwent unilateral lumpectomy or mastectomy, bilateral mastectomy, or reconstruction and were followed for 12 months. Patients also underwent radiation or chemotherapy as part of their treatment before the study and, in some cases, during participation in the study. Clinic visits were required every 3 months, with standard care treatment administered by the clinician, as well as daily fluid monitoring, using the extracellular to total body water (ECW/TBW) ratio obtained with the home device. ResultsPreliminary findings from the 8 cases showed that daily monitoring with the home device is possible, and may aid in the detection of fluid changes due to interventions like radiation or chemotherapy; these changes typically subside after treatment, compared to a permanent fluid increase that may indicate lymphedema. While one participant developed lymphedema, there is insufficient data to generalize the feasibility of early detection using the home device. A significant difference between ECW/TBW ratio measurements taken in the morning and evening (P ConclusionsThis case report shows the feasibility of daily remote monitoring for patients at risk of developing BCRL using a home bioimpedance analysis device.